Flexural and shear behaviour of precast sandwich slabs comprising thin walled steel fibre reinforced self-compacting concrete - Sousa, Christoph Fernandes (2013)
Publicado em "Rheology and processing of construction materials", ISBN 978-2-35158-137-7